Methylmalonic Aciduria in Children: Clinical Recommendations - Alexander A. Baranov; Leyla S. Namasova-Baranova; Tatyana E. Borovik; Tatyana V. Bushueva; Elena A. Vishneva; Oksana V. Globa; Nataliya V. Zhurkova; Elena Yu. Zakharova; Natal’ya G. Zvonkova; Lyudmila M. Kuzenkova; Sergei I. Kutsev; Svetlana V. Mikhailova; et al. (Педиатрическая фармакология, 2017)
Methylmalonic acidemia (aciduria) is an inherited metabolic disturbance from the group of organic acidemias (acidurias). The article presents etiopathogenetic, epidemiological, diagnostic, and therapeutic aspects of the problem. The possibilities of laboratory and instrumental diagnostic methods the tactics of dietary correction of metabolic disorders in acute and interstitial periods of the disease are described in details; features of drug treatment are outlined. The necessary information for clinical practice and patients’ everyday life is given in the article.